Studies on Lipid Profile of Chara contraria - K. Banerjee, Anup; Singhai, Mamita (Asian Journal of Chemistry, 2010)
There are scanty reports on the analysis of lipods in algae. Chara contraria, an unworked fresh water alga (Class Chlorophyceae, Phylum-Eucaryota) has been studied using HPLC. The disadvantage with the most of the methods is that the main polar lipid—phospho and galacto lipids appear together. The situation becomes even more critical in the analysis of the algae lipids, which contain much more polar class of lipids than higher plants lipids. HPLC has been found to be a better method of resolution. The advantage over TLC and TLC/FID have been discussed.